Peran Guru PAI Dalam Membentuk Karakter Religius Siswa Melalui Budaya Sekolah Di SMPNI 1 Balongan - Nisa, Fadlun (Jurnal Ilmiah Wahana Pendidikan, 2024)
This article aims to examine the role of the PAI teacher in shaping the religious character of students through the school culture at SMPN 1 Balongan. This study uses a qualitative method with a case study approach. As for the data collection techniques that researchers used in this study, namely: observation, interviews, and documents. The data validity technique that the researcher uses is the credibility test. The credibility test used by researchers is triangulation testing. The conclusion in this study is that teachers have an important role in shaping student character by providing appropriate rewards and punishments. Reward and punishment can strengthen students' positive character and help students understand the importance of positive character values. Therefore, teachers must pay attention to the basic principles of providing rewards and punishments and combine them with the development of positive character values. That way, students can grow and develop into individuals who have positive character and are beneficial to society. The teacher has an important role in shaping the character of students, not only in imparting knowledge, but also as a good role model for students. The role of the PAI teacher in shaping the religious character of students through the school culture at SMPN 1 Balongan is (1) The teacher becomes a role model for students, (2) Teachers Guide Students, (3) Teachers Provide Rewards and Punishment